MINAT MENGGUNAKAN DOMPET DIGITAL OVO: KEMUDAHAN PENGGUNAAN DAN KEPUASAN PELANGGAN - Priyatna, Eka Hendra; Pambudi, Januar Eky; Dewi, Ernawati (Universitas Muhammadiyah Tangerang, 2022)
AbstractThe purpose of this study was to determine the effect of Ease of Use and Customer Satisfaction on Interest in Using OVO Digital Wallet, either partially or simultaneously on OVO Visionet. This study uses the associative method with a quantitative approach. Sampling of 75 people. Techniques and tools for data collection is a questionnaire or questionnaire. Descriptive data analysis technique is used to describe the description of respondents' responses and data distribution, while inferential statistical analysis is used to test hypotheses. The data processing is assisted by Microsoft Excel and SPSS software version 25. Meanwhile, the contribution of Ease of Use (X1) and Customer Satisfaction (X2) to Interest in Using OVO Digital Wallet (Y) is 52.40%, the remaining 47.60% is influenced by other variables. (X) which was not researched (epsilon) but affected Interest in Using the OVO Digital Wallet (Y) which was suspected by the variables of Service Features, Sales Promotion, Risk Benefit, Trust, Website Quality, and so on. Partially, Ease of Use has a positive and significant effect on Interest in Using an OVO Digital Wallet, while Customer Satisfaction has a positive and significant effect on Interest in Using an OVO Digital Wallet.Keywords: Ease of Use, Customer Satisfaction, Interest in Using OVO Digital Wallet